Intra-specific isotope variations of franciscana dolphin Pontoporia blainvillei regarding biological parameters and distinct environments - Paso Viola, María Natalia; Riccialdelli, Luciana; Negri, Maria Fernanda; Panebianco, María Victoria; Panarello, Hector Osvaldo; Cappozzo, Humberto Luis (Mammalian Biology)
The franciscana dolphin Pontoporia blainvillei is the most endangered small endemic cetacean species of the southwestern South Atlantic Ocean. We assessed intra-specific variation in the diet of franciscana regarding biological parameters (sex, total body length, age class and sexual maturity) and between distinct environments (open marine area vs. an area adjacent to an estuary) from the Buenos Aires coast, Argentina, using both stable isotopes and stomach content analysis. We found a significant isotopic enrichment in 15N in neonates and nursing calves, representative of the lactation period. We found differences in the diet of franciscana between dolphins from the open marine area and dolphins living in waters influenced by the estuary, by both diet estimating methods. The lower δ15N values in dolphins living in waters adjacent to the estuary could be associated with a higher consumption of small sizes of the striped weakfish (Cynoscion guatucupa), which has lower isotope values than the larger sizes consumed in the open marine area. This trophic differentiation between locations is in agreement with the existence of two genetically distinct populations recently found in the study area. This study reveals geographical variations in the diet of franciscana dolphin, supporting the new delineation of distinct franciscana populations in Argentine waters. Considering the small home range and the limited movement pattern of the species, the population living near the estuary would likely need protection due to its low level of genetic diversity and feeding preferences. Therefore, the preservation and conservation of the mentioned habitat is recommended to ensure population viability of franciscana in the region. Fil: Paso Viola, María Natalia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales ...